Trace element analysis reveals bioaccumulation in the squid Gonatus fabricii from polar regions of the Atlantic Ocean. (January 2020) - Lischka, A.; Lacoue-Labarthe, T.; Bustamante, P.; Piatkowski, U.; Hoving, H.J.T.
Abstract: The boreoatlantic gonate squid ( Gonatus fabricii ) represents important prey for top predators—such as marine mammals, seabirds and fish—and is also an efficient predator of crustaceans and fish. Gonatus fabricii is the most abundant cephalopod in the northern Atlantic and Arctic Ocean but the trace element accumulation of this ecologically important species is unknown. In this study, trace element concentrations (Ag, As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, and Zn) were analysed from the mantle muscle and the digestive gland tissue of juveniles, adult females, and adult males that were captured south of Disko Island off West-Greenland. To assess the feeding habitat and trophic position of this species, stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) were measured in their muscle tissue. Mercury concentrations were positively correlated with size (mantle length) and trophic position. The Hg/Se ratio was assessed because Se has been suggested to play a protective role against Hg toxicity and showed a molar surplus of Se relative to Hg. Cadmium concentrations in the digestive gland were negatively correlated with size and trophic position (δ 15 N), which suggested a dietary shift from Cd-rich crustaceans towards Cd-poor fish during ontogeny. This study provides trace element concentration data for G. fabricii from Greenlandic waters, which represents baseline data for a northern cephalopod species. Within West-Greenland waters, G. fabricii appears to be an important vector for the transfer of Cd in the Arctic pelagic food web. Graphical abstract: Image 1 Highlights: Trace element concentrations were measured in mantle and digestive gland tissue of G. fabricii from Greenland waters. Mercury concentrations showed a positive correlation with size and trophic position. Cadmium concentrations decreased with size and suggest a diet shift with maturation. G. fabricii can be considered a vector for the transfer of trace elements in the Arctic food web.